Handbook of plant protection - Saha L.R.; Saha L.R. (Ludhiana Kalyani, 2003)
the text is designed primarly as aready reference for identification and control of pests and diseases of economic crops
pulses small millets sugar crops spices
Keywords: pulses,small millets,sugar crops